An experience in the role of links with society from the Admiral Illingworth Higher University Institute - Nivela Mesías, Gessenia Galuth; Brito Moreno, Jhon Edison; Jaramillo Hurtado, David Enrique (Revista Minerva, 2023)
Community services in higher level institutions focus on the development of the abilities and skills of different vulnerable groups in social environments that need to grow in a totally competitive space and often lack the appropriate tools. For this work, a documentary methodology was used, which served for the analysis of the need to have programs and projects for the development of community services; as well as having the documents and procedures required for them, this being the basic objective of the present investigation. With this, it is evident that the structural management of the relationship with society is complemented by the activities developed by the students.